Urban production – A socially sustainable factory concept to overcome shortcomings of qualified workers in smart SMEs. (January 2020) - Matt, Dominik T.; Orzes, Guido; Rauch, Erwin; Dallasega, Patrick
Highlights: Literature review in Industry 4.0 and socially sustainable factories. Analysis of shortage of skilled workers with a focus on SMEs. Presentation of the concept of urban production and socially sustainable factories. Set of measures for more attractiveness for young talents, mid ager and best ager. Discussion of research directions for the future. Abstract: Many of the Industry 4.0 approaches are of a technical nature, and by developing new intelligent technologies and adapting and transferring existing techniques, they will help increase productivity in industry. However, human resources will play a central role also in future factories, thus they are a key factor for implementing Industry 4.0. The role and job profile of employees in the smart factories will change in the future and it will be increasingly challenging for SMEs to compete with large corporations in the fight for skilled workers. In the smart city of tomorrow, production sites will be integrated in the sense of an 'urban production' in a city-friendly way becoming more interesting for talents and qualified work force. Thus, this paper discusses the imminent shortage of skilled workers with a focus on SMEs. The proposed concept of urban production gives an overview of measures to overcome the shortage of qualified workers. The paper aims to show that urban production is a concept to achieve a socially sustainable symbiosis between companies and the city of the future.